Air pollution burden of disease over highly populated states in the Middle East - Isaifan, Rima J. (Frontiers in Public Health, 2023)
Background: Recent epidemiological research has proven that air pollution triggers the risk of morbidity and mortality due to respiratory and cardiovascular-related diseases. More specifically, fine particulate matter with a diameter of less than 2.5μm (PM2.5) can penetrate deeply into the lung and bloodstream, causing critical adverse effects on human health. Objective: It is found that there is inadequate published research related to the health impact of ambient air pollution in the Middle East region. Some states are well studied, while others are not. This work aims to evaluate the health impact of long-term exposure to PM2.5 in the nine most populated countries in the Middle East region, with a total population of about 363 million (in 2012). Methods: In this study, the human health impacts in terms of total mortality and the estimated attributable proportion (AP) due to long-term exposure to ambient PM2.5 were estimated using the World Health Organization method and software (AirQ+). Results: In 2012, the annual median PM2.5 concentrations ranged from 34 µg/m3 in Turkey and Syria to 108 µg/m3 in Saudi Arabia. The total estimated mortalities in the nine most populated countries in the Middle East due to long-term exposure to fine particulate matter was about 152,925 (half of which are residents in Egypt). Moreover, the relative risk (RR) was the highest for Saudi Arabia at 1.8031 and the lowest for Turkey and Syria at a value of 1.1553. The highest AP (central value) was 44.5% in Saudi Arabia, while the lowest was 13.4% in Turkey and Syria. Conclusions: The results indicate a significant impact of air pollution due to long-term exposure to fine particles resulting in early mortality. This urges the collaboration between the governments and different sectors to adopt stringent regulations to reduce the anthropogenic sources related to traffic and industrial emissions in the Middle East in order to reduce the health burden of air pollution.